2022
DOI: 10.1016/j.electacta.2021.139537
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the performance losses and “invasiveness” of in situ characterization steps during carbon corrosion experiments in polymer electrolyte membrane fuel cells

Abstract: Carbon corrosion represents one of the most critical degradation mechanisms within state-of-the-art polymer electrolyte membrane fuel cells. Its most prominent consequences include the loss of electrochemical active surface area (ECSA), porosity, and electrical contact within the electrode. The present study seeks a detailed understanding of the dependence between the polarization performance losses and the individual loss terms, both as a function of the amount of corroded carbon. A simplified onedimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The C‐corrosion causes overall MEA degradation and severe PEMC performance decay attributed to the decrease in mass transport, collapse of the pore structure, loss of hydrophobicity, breakdown of catalyst connectivity, and reduced electrochemical active surface area (ECSA). The choking of the pore network by the carbon aggregates hinders mass transport [25,110–114] …”
Section: Fuel Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…The C‐corrosion causes overall MEA degradation and severe PEMC performance decay attributed to the decrease in mass transport, collapse of the pore structure, loss of hydrophobicity, breakdown of catalyst connectivity, and reduced electrochemical active surface area (ECSA). The choking of the pore network by the carbon aggregates hinders mass transport [25,110–114] …”
Section: Fuel Cellsmentioning
confidence: 99%
“…Compared to the potential cycling AST, start/stop cycling is shown to cause substantial C‐corrosion [118–123] . The measurement of actual carbon loss and the evaluation of PEMC performance degradation (current density reduction and ECSA loss) were typically followed in the different AST protocols [112,121,124] . Distribution of relaxation time (DRT) investigation showed that the degradation behaviours vary with the type of AST used.…”
Section: Fuel Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18] In other studies, the whole membrane electrode assembly (MEA) is studied after applying some sort of accelerated stress test (ASTs). [19][20][21][22] Thus, not many studies analyse PEMFC degradation after operation in realistic conditions for thousands of hours. 23 Furthermore, in these long-term studies, the inhomogeneities in the degradation process (e.g.…”
Section: Introductionmentioning
confidence: 99%